Mapping units based on spatial uncertainty of magnetic susceptibility and clay content - Teixeira, Daniel D.B.; Marques, José [UNESP]; Siqueira, Diego S. [UNESP]; Vasconcelos, Vinicius; Carvalho, Osmar A.; Martins, Éder S.; Pereira, Gener T. [UNESP] (Elsevier, 2018)
This study aimed to use spatial uncertainty of magnetic susceptibility (MS) and clay content to improve soil-mapping units. In an experimental area of 870 ha, a regular sampling grid containing 371 points was set, in which MS and clay content were assessed at a depth range of 0–0.25 m. Using a digital elevation model and field observations, a 4440-m transect was established on the study area from hilltop to the foothill, toward the gentlest slope. Standard deviation maps based on 200 realizations of the sequential gaussian simulation measured spatial estimate uncertainties. To limit transition zones along the transect, uncertainty isolines representative of the transition between soil-mapping units were selected. Both attributes presented peaks of uncertainties near the change of mapping units, previously known. Uncertainty zones, previously delineated, ranged from 45 to 210 m and from 60 to 170 m, for MS and clay content, respectively. However, after extrapolating the uncertainties to the side of the transect, amplitude changes of the uncertainty zones were observed, especially in the transition regions between landscape shape and geology. Delineation of mapping units, which incorporated the uncertainties of MS and clay content, was similar. However, due to lower cost and promptness, MS becomes the most feasible alternative. Knowing spatial uncertainties enables readjusting limits in maps of soil-mapping units and may support identification of most favorable regions for determining modal pedon representative of each unit.
Keywords: Geostatistics; Pedometrics; Sequential Gaussian simulation